Analisis Kondisi Ekowisata Mangrove Belawan Sicanang di Kecamatan Medan Belawan, Kota Medan - Restu Restu; Meilinda Suriani Harefa; Asnimar Duha; Anggi Violin Sinabutar; Edoy Nainggolan; Febbry Vebilola Manalu; Lisna Anggia Fortunata (Fakultas Teknik Universitas Cenderawasih, 2024)
Mangroves are plants that live in coastal areas which have great benefits, namely as abrasion barriers, wave breakers, as a food source for marine biota, absorbing carbon dioxide, and producing oxygen. Sicanang Mangrove Ecotourism is a mangrove forest that is open to the public to visit this ecotourism. The location is in Belawan Sicanang Village, Medan Belawan District, Medan City. Data collection techniques were used to obtain primary data and secondary data through observation, interviews and literature study. Research data was analyzed using qualitative descriptive analysis. The research results show that since 2020, this ecotourism has been closed and is not being maintained to this day. The cause of the damage to ecotourism is due to the local community's lack of understanding about developing mangrove ecotourism in the area, such as cutting down mangrove trees for wood as furniture material. This causes damage to the mangrove ecosystem and the quantity of mangrove trees decreases. It was concluded that the damage was caused by a lack of attention to repairs from the government and management awareness from the local community.